LEVERAGING THE UBIQUITOUS GPS SENSOR ON THE SMARTPHONES FOR ACCESSIBLE LAND SURVEYING - Habibullah, Ahmad Dhuha; Yuliza, Elfi; Almadi, Ismail Fahmy; Intara, Yazid Ismi; Ekawita, Riska (Universitas Mataram, 2025)
The Global Positioning System (GPS) is an essential tool in land surveying. GPS has become an alternative method of surveying that requires less manpower and less time. However, GPS devices are still expensive to buy, especially for students. On the other hand, almost every student has a smartphone with a built-in GPS sensor, so this GPS is certainly accessible to everyone with a smartphone. This study used a smartphone's GPS to conduct land surveying at the campus of Bengkulu University. This smartphone’s GPS was used to track various parameters such as coordinates, elevation, and distance between two or more points to calculate the area within the study area. The innovative method of using the built-in GPS sensor in smartphones will provide convenience for users and introduce simplified open-source software for the land measurement process. The measurement was calibrated using a conventional roll meter to verify the linear error by comparing the two measurements between the smartphone’s GPS and roll meter. The smartphone’s GPS reading was logged using GPS Waypoints and My Tracks, free Android applications on the Google Play store. This study's average error in measurements obtained using GPS on smartphones was 3.02%. This value is sufficient for the initial stage of low-cost land surveys and falls within ideal conditions for GPS measurements. Therefore, this article emphasizes the potential of smartphone GPS to optimize techniques in education and scientific investigations.